Die Joyce-Rezeption in der deutschsprachigen Erzählliteratur nach 1945 - Jäger, Maren (Studien zur deutschen Literatur ;, 2009)
No novel written in English had such an intensive influence on 20th century German prose writing as Ulysses by the Irish writer James Joyce. After the caesura of the Second World War, authors such as Wolfgang Koeppen, Arno Schmidt, Uwe Johnson and Wolfgang Hildesheimer derive inspiration from the re-discovery or new discovery of international modernism. This study sets itself the aim of tracking the paths and traces of this influence and developing the specific premises and positions of the authors examined.